1985
DOI: 10.1128/jb.162.3.1329-1331.1985
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and characterization of Pseudomonas aeruginosa mutants that hyperproduce exoproteins

Abstract: We isolated two mutants of Pseudomonas aeruginosa PAO with defective iron uptake. In contrast to the wild-type strain, the mutants produced extracellular protease actity in media containing high concentrations of salts or iron and hyperproduced elastase, staphylolytic enzyme, and exotoxin A in ordinary media (Xch mutants). The mutations were located in the 55' region of the chromosome, between the markers met-9011 and pyrD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…They suggested that previous reports of inhibition by ammonium ions represented a non-specific effect, most likely related to the high ionic strength of the medium. Recent work supports their conclusions (Fairbairn, 1984;Bjorklind et al 1985).…”
Section: Experimental Observation Of Induction and Repression Of Extrsupporting
confidence: 56%
“…They suggested that previous reports of inhibition by ammonium ions represented a non-specific effect, most likely related to the high ionic strength of the medium. Recent work supports their conclusions (Fairbairn, 1984;Bjorklind et al 1985).…”
Section: Experimental Observation Of Induction and Repression Of Extrsupporting
confidence: 56%